TEACHING FUNCTIONAL SPEECH STYLES IN RUSSIAN AS A FOREIGN LANGUAGE LESSONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The article explores the significance of teaching functional speech styles in Russian as a Foreign Language (RFL) classes. It analyzes approaches to the development of stylistic competence and provides recommendations for the effective organization of style instruction within the context of students' academic and professional training.